Stochastic Models on Time to Recruitment in a Two Grade Manpower System using Different Policies of Recruitment - P. Mariappan; S. Dhivya, A. Srinivasan, (Recent Research in Science and Technology, 2011)
In this paper a two grade organization in which depletion of manpower occurs due to its policy decisions is considered. Two mathematical models are constructed employing two different univariate recruitment policies, based on shock model approach. The mean and variance of the time to recruitment are obtained for both the models under different conditions. The analytical results are numerically illustrated and relevant conclusions are presented.